Conceptualizing Individual and Household Disaster Preparedness: The Perspective from Cameroon - Nojang, Emmanuel Nzengung; Jensen, Jessica (International journal of disaster risk science, 2020)
This research explored the basic issue of what preparedness means and entails to people in Fako Division, Cameroon—a place threated by many hazards and that has experienced many disasters. Findings from the analysis of the 33 interviews conducted in this study indicate that preparedness is a dynamic state of readiness that is dependent on context, a social process, and a process of completing activities to save lives and minimize the effects of disasters. In addition, the research determined that Cameroonians view a wholly prepared person as someone who would: (1) have knowledge about hazards and what to do about them; (2) engage others, including their families and neighbors, in discussions about activities related to hazards; and (3) participate in activities to minimize loss from hazards, sustain themselves in the face of hazards, and flee from hazards. The findings from the interview data synchronize to a large extent with what is implied, but not clearly stated, in the existing research literature. The article addresses this synchrony, posits a definition of preparedness, and identifies the theoretical components of preparedness.